Two-Stage Optimization of Fluidized-Bed Powder Coating for Continuous Carbon Fiber-Reinforced Polyetheretherketone (CF/PEEK) Towpregs - Yigit, Yusuf; Dogu, Mustafa; Eksi Altan, Mihrigul (MDPI, 2026)
Solvent-free, continuous manufacture of carbon-fiber/poly(ether ether ketone) (CF/PEEK) towpregs via fluidized-bed powder coating requires stable powder fluidization together with controllable coating residence time. A laboratory-scale continuous coating line comprising a creel, guiding/tension rollers, a vibrated fluidized-bed coater, as well as a take-up unit was designed and commissioned. Subsequently, a two-stage optimization and modeling framework was developed. First, PEEK powder fluidization was optimized using a Taguchi L9 design, varying air pressure (P), powder weight (W), and vibration frequency (f); bed expansion ratio (epsilon) and average surface bubble diameter (Db) were measured and ANOVA identified air pressure as the primary contributor to epsilon (83.4%), establishing a stable operating window. Second, within this window, coating performance was assessed by varying line speed (Vline) and coating-roller position (Hr) in 12 runs and combining them into a geometry-based residence time (Rt) for simplified control. Coating quality was quantified based on fiber volume fraction (Vf) and composite tensile strength (sigma c) after consolidation. The best condition in the tested range was Hr=0.5 cm and Vline=1.5 m/min (Rt=0.54 s), achieving 61.5% Vf and 1800.5 MPa tensile strength. The resulting mathematical models predicted Vf and sigma c with good accuracy (R2 >= 0.92), supporting parameter selection and process optimization for continuous CF/PEEK towpreg production.
Keywords: carbon fiber/PEEK towpreg; coating residence time; continuous manufacturing; fluidized-bed powder coating; multiple regression modeling; taguchi design; MECHANICAL-PROPERTIES; PARAMETERS; FINE; PRESSURE; SIZE; Engineering